Responsivitas Pelayanan Publik Dinas Perhubungan Kota Malang terhadap Tingginya Tingkat Pengaduan Masyarakat - Hendra Hafid Risalbi; Yaqub Cikusin; Hayat Hayat (Nakhoda: Jurnal Ilmu Pemerintahan, 2021)
Responsiveness is a form of sensitivity and ability of the government in providing services, including in the provision of services to public complaints made by the Malang City Transportation Service. This article aims to determine the responsiveness of the Malang City Transportation Service to the high level of public complaints and the inhibiting factors. To find out this type of research is descriptive - qualitative, with interview, observation, and documentation data collection techniques. This article shows that the responsiveness of the Malang City Transportation Service is quite responsive, this is evidenced by the decrease in the level of public complaints every month, especially in 2020. In addition, the responsiveness of the Malang City Transportation Service can also be seen from the service quality indicators, namely: (1) Tangible or physical evidence, (2) Reliability or reliability, (3) Responsiveness or responsiveness, (4) Assurance or assurance, and (5) Empathy or empathy. However, in the implementation of these services, there are obstacles, namely the number of people who do not understand the procedure for reporting complaints, the existence of complaints that are not in accordance with the facts on the ground, the existence of people who often demand speedy handling from agencies, and frequent miss communication to the public which has an impact on delays handling time.